Development Of Crimp Connector And Splice-Insulating Kit For Trailing Cables - Walter J. Frank (The National Institute for Occupational Safety and Health (NIOSH), 1979)
Thls report summarizes work done under Bureau of Mines contract H0357100, "Development of a Crimp Connector for Trailing Cable Splices." The purpose of this effort was to establish optimum connector design conditions to meet flex cycle, pullout and electrical resistance criteria on phase power conductors. Field testing of "optimum design" connectors is briefly discussed. One of the primary objectives of contract H0357100 was to enable one to design better performing phase conductor connectors. Illustrating the practical significance of this 1s a discussion on the development of a new splice kit for trailing cables. The connectors in this kit were designed in accordance with the design methods described in the contract final report. Kit components, test data, and a connector installation tool are also discussed. The successful effort on the phase connector has resulted in contract H0377042, entitled "Design and Testing of Joining Sleeves for Trailing Cable Ground and Pilot Wires." The purpose of this contract (currently in effect) is to improve ground-conductor and pilot-wire performance. Significant findings to date are discussed.